ظاهرة اليوتيوبرز النسائية دراسة ميدانية لعينة من نساء ولاية الأغواط - شقنان سهام; لرقط عائشة; طلحة بشير (My University, 2022)
تناولت هذه الدراسة موضوع اليوتيوبرز النسوي في ولاية الأغواط ، فمع تطور العلوم والتكنولوجيا وتغير ظروف المعيشة ، تبعا لذلك أصبح الإبداع و الإبتكار هما الصفة الغالبة في الأفراد ، و أصبح المجتمع اليوم مطالب بتأدية الكثير من الواجبات التكنولوجية المعقدة والدقيقة و الذي يتطلب أن يكون في مستوى معين من التحصيل الدراسي و العلمي حيث يحتاج الأفراد إلى مستوى أعلى من التعليم كلما ازدادت أساليب و أدوات ووسائل الإنتاج دقة وتعقيدا. وبما أن موقع اليوتيوب هو الأساس الذي ترتكز عليه المجتمعات في التفاعل و التشارك ، فإن النظرة الحديثة لم تعد تعتبره مجرد خدمة عامة تقدمها الشركات كما كان عليها الأمر من قبل، بل أصبح عملية إستثمار طويلة الأجل ومضمونة العائد ، ويشكل اليوتيوب في العصر الراهن أهم عنصر من عناصر تثقيف البشرية لذا فإنه من الضروري أن ينسجم أي توجه لوضع الأسس و السياسات والاستراتيجيات لهذا النوع من المواقع المهمة في الحياة مع الإطار العام و الخطوط العريضة لسياسات واستراتيجيات أعم بظاهرة اليوتيوبرز بمفهومها الواسع . وبتعبير آخر فقد أصبحت ظاهرة اليوتيوبرز سمة من سمات العصر الحديث ، خصوصا في ظل ما يشهده العالم من تفجر معرفي وتقني في كافة المجالات خاصة في تنوع وسائل التواصل الإجتماعي وما يترتب عليه من تغيرات متسارعة في فتح قنوات عبر اليوتيوب This study dealt with the issue of feminist YouTubers in the state of Laghouat, with the development of science and technology and the change of living conditions, accordingly, creativity and innovation became the dominant characteristic in individuals, and society today is required to perform many complex and precise technological duties, which require that it be at a certain level. From academic and scientific achievement, as individuals need a higher level of education as the methods, tools and means of production become more accurate and complex. Since YouTube is the basis on which societies depend on interaction and participation, the modern view no longer considers it just a public service provided by companies as it was before, but has become a long-term investment process with a guaranteed return, and YouTube in the current era constitutes the most important element of Elements of educating humanity, so it is necessary that any orientation to lay the foundations, policies and strategies for this type of important sites in life be consistent with the general framework and outlines of policies and strategies more generally in the phenomenon of YouTubers in its broad sense. In other words, the phenomenon of YouTubers has become a feature of the modern era, especially in light of the knowledge and technical explosion that the world is witnessing in all fields, especially in the diversity of social media and the rapid changes that result in the opening of channels through YouTube.